The theatre career of Manuel Linares Rivas (Castilla. Estudios de Literatura, 2022)
In this study, I analyze the theatrical career of Manuel Linares Rivas according to his social commitment. It is argued that the author maintains ideological coherence throughout his career as a playwright in favor of breaking the pact between the nobility and the big bourgeoisie. At the same time, he is a defender of an alliance between the petty bourgeoisie and the proletariat. Taking into account also his renewal eagerness of the staging, it is proposed that Linares Rivas be assigned to the roster of novadores authors of the first third of the 20th century.
Keywords: social drama; 20th century; history of theatre; Bourbon Restoration; radical bourgeoisie